Integrative research reviews: Considerations for perioperative nursing research - Michael, Rene; Della, Phill (Cambridge Publishing, 2012)
Integrative research reviews (IRRs) are a valuable part of the process of creating and organising a body of literature by synthesising and analysing the results from independent studies. IRRs have great potential for clarifying the theoretical perspective and substance of perioperative nursing as well as enabling nursing research-based knowledge to be more accessible to clinical nurses. The purpose of this paper is to define and present an overview of IRRs. Methods and stages are made known for undertaking this technique including the practice of the same standards of clarity, rigour and replication used for primary research. It is suggested that perioperative nurses should consider this kind of review in order to enhance the development of nursing science in their speciality.